Data Mining implementation on SMUN Scholarship recipient candidates using the C4.5 algorithm - Rusdiansyah, Rusdiansyah; Supendar, Hendra; Suharyanti, Nining; Tuslaela, Tuslaela (Politeknik Ganesha Medan, 2022)
This research is motivated by SMUN previously only providing scholarships for underprivileged students, while for students who excel, the method is not yet, therefore, research by implementing data mining with the C4.5 algorithm method so that in the future, if the scholarship program is for outstanding students already exists, then SMUN can immediately apply it. The sample data are 33 scholarship recipients with subjects that have been determined based on the report card scores of prospective scholarship recipients. The selection results for receiving scholarships to outstanding students so far have only been calculated in general terms, the possibility of incorrect results will cause losses for students who have good achievements. As a result, there are students who should get the scholarship rights and do not receive it. The problem of this research is how to make it easier to analyze students who need and are entitled to receive scholarships, how to make it easier to select and determine scholarship recipients. The research uses the C4.5 algorithm to overcome these problems. With the C4.5 algorithm, the percentage accuracy value can be calculated which is used to determine whether the student is entitled to receive a scholarship or not. The data collection technique in this study is to use student report cards. classification value in determining students who get scholarships with the highest accuracy of 81.81%. The accuracy value was obtained by experimenting with the testing process with the number of student data as many as 33 students. It is hoped that it will make it easier to receive scholarships for students who excel academically in school.